Synergistic in vitro activity of sodium houttuyfonate with fluconazole against clinical Candida albicans strains under planktonic growing conditions - Jing Shao; YanYan Cui; MengXiang Zhang; TianMing Wang; DaQiang Wu; ChangZhong Wang (Taylor & Francis Group, 2017)
Context: Fluconazole resistance is an intractable problem of treating Candida albicans, calling for more antifungal agents to enhance the activity of fluconazole. Objective: This work investigates the anti-C. albicans activities of sodium houttuyfonate (SH) and/or fluconazole and the associated mechanism. Materials and methods: The minimum inhibitory concentrations (MICs) of SH and fluconazole both ranging from 0.5 to 1024 μg/mL were determined by broth microdilution method in 19 C. albicans isolates, and their fractional inhibitory concentration index (FICI) was evaluated by checkerboard assay. After MICSH and/or MICfluconazole treatments, the expressions of IFD6, PHR1, ZAP1, ADH5, BGL2, XOG1 and FKS1 were analyzed by quantitative reverse transcription polymerase chain reaction (qRT-PCR) in C. albicans 1601. Results and conclusion: The MICs of SH alone ranged from 32 to 256 μg/mL and decreased 2-16-fold in combination. SH showed strong synergism with fluconazole with FICI <0.13-0.5. In C. albicans 1601, we observed that (i) the expression of the seven genes increased notably in a range between 3.71- and 12.63-fold (p < 0.05) when SH was used alone, (ii) the combined use of SH and fluconazole slightly inhibited the expression of IFD6 and PHR1 by 1.23- and 1.35-fold (p > 0.05), but promoted evidently the expression of ZAP1, ADH5, XOG1 and FKS1 by 1.98-, 3.56-, 4.10- and 2.86-fold (p < 0.05). The results suggested SH to be a potential synergist to enhance the antifungal activity of fluconazole in C. albicans resistant isolates, and the underlying mechanism may be associated with β-1,3-glucan synthesis and transportation.